The interaction of judge’s behavior and judge’s decision prognosis in the procedural justice judgments - Laurinavičius, Alfredas (Psichologija, 2005)
Psychological research shows a big importance of procedural justice in dispute resolution. Perception of procedural justice affects evaluations of the performance of legal institutions and authorities, evaluations of legal decisions and outcomes, satisfaction with encounters with the legal system, support for legal institutions and compliance with law. According to K. van den Bos and E. A. Lind people are more affected by variation in fairness when they feel uncertain. Participants’ expectations about judge’s possible decision can moderate relationship between procedure and subjective evaluation of procedural justice. 3 × 2 × 2 factorial experiment was conducted: 3 (expectation of the possible decision: certainly positive, certainly negative, uncertain)× 2 (decision: positive vs. negative) × 2 (procedure: fair vs. unfair). The experiment was conduced in 2 Vilnius universities, participation was voluntary, participants were not paid. Data of 330 students (men and women) were analyzed. There were between 22 and 36 participants per cell. A scenario method was applied in the experiment. Participants were given a description of legal dispute of non material harm compensation. Participants were asked to imagine themselves as being defendant and evaluated a possibility of positive and negative decision. Participants were shown one of two videotapes with excerpts from litigation session. After watching the excerpt (fair treatment or unfair treatment) they received judge’s final decision (favorable or unfavorab le) and completed the questionnaire. Dependents variables in this experiment were participants’ evaluations of distributive justice, procedural justice, perceived voice, neutrality, trust in benevolence, status recognition and support for courts.A 2 × 2 × 3 ANOVA revealed significant interactions between Expectation and Procedure on perceived voice F (2,318) = 4.513, p < .05, η² = .028, neutrality F (2,318) = 3.413, p < .05, η² = .021 and support for courts F (2,318) = 3.084, p < .05, η² = .019. No interactions were found for distributive justice, procedural justice, trust in benevolence, status recognition. A significant effect of Expectation was found on distributive justice judgments F (2,317) = 5.02, p < .05, η² = .031. Those expected negative decision rated distributive justice more positively.The presented research shows that expectation of judge’s decision can moderate some procedural justice judgments and support for courts judgments. Variation of procedure had biggest effect on evaluation of perceived voice, neutrality and support for courts in condition when participant was expecting negative decision. It seems that expectation of negative decision makes people more sensitive to procedural issues. Being certain about positive decision decreases a role of procedure on those ratings.
Keywords: psychology of justice; procedural justice; dispute resolution